Comparison of efficacy and safety of doxycycline versus azithromycin for mycoplasma pneumonia in children over 8 years old - WANG Shengquan, HUA Ying, SUN Mingxia, MA Jiawei, ZHANG Weihon,g WU Guoqin, LIU Ji (Zhongguo linchuang yanjiu)
"Objective To compare the efficacy and safety of oral doxycycline and azithromycin in the treatment of children with a tendency to refractory Mycoplasma pneumoniae pneumonia（RMMP）. Methods A total of 94 MMP children over 8 years old with C reactive protein≥22.86 mg/L who were treated in the outpatient department of Akqi County People’s Hospital from April to December 2023 were selected as the prospective research objects. They were randomly divided into azithromycin group and doxycycline group with 47 cases in each group. The efficacy after 5 days of treatment, body temperature recovery within 72 h, and adverse reactions were compared between the two groups. Results The total effective rate of the doxycycline group was higher than that of the azithromycin group, with a statistically significant difference (93.62%vs 73.91%,χ 2=6.672,P ＜0.05). The incidence of adverse reactions in the azithromycin group was lower than that in the doxycycline group, but the difference was not statistically significant ( P ＞0.05). There were no serious adverse reactions in the two groups. At 48, 72, 96, and 120 hours after treatment, the proportion of the children whose body temperature returned to normal in the doxycycline group was higher than that in the azithromycin group, with a statistically significant difference ( P ＜0.05). Conclusion For children over 8 years old with RMMP tendency, doxycycline has advantages over azithromycin in efficacy and temperature improvement, and is safe and reliable."